A Thinker for a Theater: Buero Vallejo - Huerta Calvo, Javier (Escritura e Imagen, 2024)
The Theatre of Antonio Buero Vallejo stands out for its literary and scenic qualities, as well as for its profound thought. The philosophy is very present in his plays: Plato, Schopenhauer, Nietzsche, Unamuno, Ortega y Gasset, Zubiri, Camus...